Progranulin deficiency leads to severe inflammation, lung injury and cell death in a mouse model of endotoxic shock. Issue 3 (12th January 2016) - Yu, Yuan; Xu, Xiaoying; Liu, Lu; Mao, Sheng; Feng, Tingting; Lu, Yi; Cheng, Yizhe; Wang, Hongyan; Zhao, Weiming; Tang, Wei
Abstract: Progranulin (PGRN) is a crucial secreted growth factor involved in various kinds of physiologic and disease processes and often has a protective role in inflammatory diseases. This study was designed to investigate the protective effects of PGRN on endotoxic shock in a mouse model of PGRN deficiency. After lipopolysaccharide (LPS) injection to induce endotoxic shock in mice, PGRN levels were induced in wild‐type (WT) mice at 6 and 24 hrs. Survival rate analysis, haematoxylin and eosin staining, immunohistochemical staining, enzyme‐linked immunosorbent assay and in situ terminal deoxynucleotidyl transferase–mediated uridine triphosphate nick‐end labelling assay were used to reveal the susceptibility, lung injury, inflammatory cell infiltration, production of inflammatory mediators and lung cell death in mice after LPS injection. PGRN‐deficient ( Grn −/− ) mice were highly susceptible to LPS‐induced endotoxic shock, with decreased survival, severe lung injury, increased production of pro‐inflammatory mediators, and inflammatory cell infiltration and apoptotic death in the lung. Additionally, recombinant PGRN (rPGRN) administration before LPS stimulation ameliorated the survival of and abnormalities in both WT and Grn −/− mice. Altogether, these findings indicate that PGRN may be a novel biologic agent with therapeutic potential for endotoxic shock probably by inhibiting LPS‐induced systemic and local inflammation in mice for treating endotoxic shock.